2007
DOI: 10.1001/archpsyc.64.11.1305
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Maternal Education and Nonmaternal Care Services in the Prevention of Children's Physical Aggression Problems

Abstract: Context: Physical violence is an important health problem, and low maternal education is a significant risk for the development of chronic physical aggression (PA). We hypothesized that nonmaternal care (NMC) services could prevent the development of childhood PA problems, depending on the age at which the services are initiated. Method:Children who followed a trajectory of atypically frequent PA between 17 and 60 months of age among a population sample of 1691 Canadian families were identified. Maternal educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
113
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 131 publications
(122 citation statements)
references
References 47 publications
(61 reference statements)
4
113
1
2
Order By: Relevance
“…[147][148][149][150] Protective factors might also mitigate early influences on the neurochemical correlates of risk, including those mediated through 5-HT genes. 151 Multiple other biological adaptations that may promote resilience have also been identified.…”
Section: Role Of Protective Factors and Resilience And Other Limitatmentioning
confidence: 99%
“…[147][148][149][150] Protective factors might also mitigate early influences on the neurochemical correlates of risk, including those mediated through 5-HT genes. 151 Multiple other biological adaptations that may promote resilience have also been identified.…”
Section: Role Of Protective Factors and Resilience And Other Limitatmentioning
confidence: 99%
“…It is important to note that participants' mean age was 4 years and 1 month, and the literature has shown that children between 2 and 4 years of age present a higher frequency of aggressive behaviors when compared to younger children, between 0 and 2 years (Alink et al, 2006;Côté et al, 2007). Conversely, from the age of 4, it is possible to notice a decline in the number of aggressive events, mainly due to advances in self-regulation, associated, in turn, to the development of executive functioning and social cognition, typical of this age.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, longitudinal studies show that the first manifestations of aggression by a child occur, in general, between the first and second years of life and there is a peak of aggressiveness between the end of the third and beginning of the fourth year (Alink et al, 2006;Côté et al, 2007). Furthermore, in contrast to the popular belief that aggressiveness always increases with age, there is strong evidence suggesting that aggressive behavior tends to decrease with time, as children acquire self-regulation strategies during preschool and, consequently, learn to inhibit aggressiveness (Nagin & Tremblay, 1999;Thompson & Goodwin, 2007).…”
mentioning
confidence: 99%
“…La première grossesse d'une jeune fille qui a échoué à l'école et qui vit en situation de pauvreté devrait attirer au moins autant de ressources des services publics que les ressources investies pour un adolescent violent. D'ailleurs, les résultats de l'étude de Côté et al [7] publiée dans ce numéro et de quelques essais cliniques randomisés célèbres vont dans ce sens [14,17].…”
Section: Implications Pour La Prestation De Services Et Pour L'élaborunclassified